Gamification as a Tool for Promoting Physical Exercise and Healthy Eating Habits in Healthcare Worker Women: Effects on Cardiometabolic Health and Physical Fitness at Workplace - Gimenez, Lucas B. [UNESP]; Teixeira do Amaral, Vanessa [UNESP]; Locato, Gabriel [UNESP]; Marçal, Isabela R.; Ferron, Artur J. T. [UNESP]; Ciolac, Emmanuel G. [UNESP] (SAGE Publications, 2024)
Purpose: To evaluate the effectiveness of gamified versus nongamified health promotion interventions on cardiometabolic health and fitness parameters in healthcare worker women. Design: Randomized parallel group trial. Setting: A public outpatient health center in Brazil. Subjects: Women employees (included: n = 29; lost to follow-up: n = 1; analyzed: n = 28). Interventions: 8 weeks of gamified (n = 15) or nongamified (n = 13) interventions, consisting of health lectures, nutritional counseling, and supervised exercise training. The gamified group was divided into teams that received points based on completion of health goals/tasks. Measures: Anthropometric, cardiometabolic and physical fitness parameters. Analysis: Two-way ANOVA with repeated measures (group vs. time), and Bonferroni post hoc tests. Results: Body mass (-1.5 ± 1.5 kg), waist circumference (-1.6 ± 3.0 cm), HbA1C (-.2 ±.3%), triglycerides (-21.5 ± 48.2 mg/dl), systolic (-11.1 ± 7.9 mmHg) and diastolic (-7.1 ± 5.8 mmHg) blood pressure, as well as sit and reach (3.9 ± 3.0 cm) and six-minute walking (56 ± 37 m) performance improved (P <.05) only after the gamified intervention. Sit-to-stand performance improved after both the gamified (-1.18 ± 1.24 s) and nongamified (-1.49 ± 1.87 s) interventions. Conclusion: The gamified intervention was more effective than the nongamified intervention for improving cardiometabolic and physical fitness parameters, suggesting that gamification may be an effective tool for promoting health in healthcare worker women.
Keywords: cardiometabolic risk factor; educational program; gamification; physical activity; physical functional performance; women’s health